PERBEDAAN KADAR ALBUMIN PADA SERUM LIPEMIK DENGAN DAN TANPA PENAMBAHAN FLOKULAN GAMMA-SIKLODEKSTRIN INKUBASI 23 oC - Budi Setiawan; Rizali Noor Maulana; Subrata Tri Widada (UPPM Poltekkes Kemenkes Ternate, 2017)
Lipemic serum caused by lipoprotein particles such as cylomicrons, VLDL (Very Low Density Lipoprotein) and triglycerides. Visually, the turbidity in lipemic serum will be obvious with triglyceride levels above 300 mg / dl. This situation causes interference chromophoric in photometric analysis, interference on the wavelength and light scattering caused by the presence of lipid particles. One of them needs to be tackled by flocculation using gamma-cyclodextrin which incubation at 23oC so that the examination results to be accurate. This study aims to determine and differences albumin’s level in lipemic serum with and without addition of gamma-cyclodextrin which incubation at 23oC. The study's pre experimental use research design static group comparison. The samples were all lipemic serum many as 20 samples. The research findings was the albumin levels without adding the flocculant Gamma-cyclodextrin which incubation at 23oC was 3,77 g/dl. Where as the albumin levels with adding the flocculant Gamma-cyclodextrin which incubation at 23oC was 5,20 g/ml. The difference of albumin levels with or without adding the flocculant Gamma-cyclodextrin which incubation at 23oC was 1,44 g/dl (43 %).